PENGARUH MEDIA SOSIAL, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA USAHA MILODYA BUKET SAMALANGA BIREUEN - Muzlifa, Lola; Azhari, Azhari; Saleh, M. (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2025)
The study measures the extent to which the impact of social media, product quality factors and service quality on consumer satisfaction. A survey was conducted on 63 consumers at the Milodya Buket Samalanga business in Bireuen district. Using quantitative methods and statistical analysis with multiple regression. The results found that: (1) using social media has a significant and positive effect on consumer satisfaction, as well as product quality and service quality contribute positively to increasing consumer satisfaction at the Milodya Buket Samalanga Bireuen business. (2) Simultaneously, the presence of social media, product quality factors and service quality convincingly contribute to consumer satisfaction by 72.2%. Based on the results of this study, it is recommended for further researchers to maintain consumer satisfaction by maintaining these three factors. in order to be effective in increasing sales.